Status of food consumed in the Great Jamahiriya in terms of food additives and pollutants - Abdolgader, Ramadan E.; El-Fergani, Salem O.; Ardia, Yahya Khamis (Al-Mukhtar Journal of Sciences, 2001)
The controlling agencies of food have a great role in insuring the safety and quality of foods for consumer protection. The presence of food additives in different kinds of food is quite obvious these days. The food additives usually used to serve many technical purpose i.e. increasing the shelf life and\or improving the physical-chemical properties of foods however the consumption of un-permitted and permitted additives in excessive quantities may pose long-term health effect from our study of the status of food present in local Libya market through surveying the results that obtained from the analysis of different food staff specially those who delivered from the eastern border, the obtained results showed that most food additives were preservatives compounds such as sulfur dioxide and sodium benzoaite. The obtained results also indicated an extensive use of artificial color without mentioning the presences of these colors on the labels. Some samples showed the presence of aflatoxins specially in legume samples, the results also indicated that some samples were contained heavy metals such as lead, copper and iron more than the accepted rang, however the results did not show any pesticides, nor radioactive materials tested samples.